330 The impact of specialist practioners within an english ambuilance service. (1st May 2022) - Spaight, R; Clarke, R; England, L; Fryer, C
Abstract : Background: Specialist Practitioners were introduced to East Midlands Ambulance Service in September 2020. Three Cohorts of SP's have been introduced who have undertaken additional training and education in order to assess minor illness and injuries which may reduce the need for a visit to accident and emergency department. Method: Analysis of the clinical analytics data suite matched to the Call data sets and compared with wider cohorts of paramedics to understand the impact of each of the three cohorts since their introduction to the Trust. Results: Specialist Practitioner(SP) n=37 have attended (n=16, 557) conveyed 36.73% (n=6082) EMAS 44.41% SP variance -7.68%, cohort 1 (CH1) commencement date 28/09/20 n=12 (n=7731) conveyed 33.07% CH1 variance -11.34%, Category 1 calls 48.93% (EMAS 56.88% Variance -7.95%) Category 2 calls 38.66% (EMAS 57.95 Variance -19.29) Category 3 calls 22.41% (EMAS 32.31% Variance -9.90) Cohort 2(CH2) commencement date 19/10/20 n=12 have attended (n=6103) conveyed 42.08% (n=2568) SP variance -2.33, Category 1 calls 57.22% (Variance +0.32) Category 2 calls 50.16% (EMAS 57.95 variance -7.79) Category 3 calls 30.12% (EMAS 32.31 variance -2.19). Cohort 3(CH3) commencement date 20/07/21 n=13 have attended (n=2716) conveyed 35.20% (EMAS 44.41 variance -9.21) Category 1 calls 52.97% (Variance -3.91) Category 2 calls 39.51% (Variance -18.44) Category 3 calls 22.99% (variance -9.32). SP Cohort all category variance (33.07 – 42.08). Conclusion: The initial three cohorts have all provided significant impact on the conveyance rate of the patient's seen. As this role becomes more embedded the true benefits will be seen through reduced conveyance and support for other crews on the front line. Conflict of interest: None. Funding: Internal.